(untitled) - Keith Boeckner (Đà Nẵng, 1996)
The book consists of two parts. Part one is student's book. There are a range of authentic texts and listening activities covering every thing from the lastest applications of computer technology to the underlying computer processes and components. Part two is answer book. It contains a key to the tasks and exercises, the tapescripts, and useful unit-by-unit teaching notes
Keywords: English language,English language; Textbooks for foreign speakers,Technical English